2005
DOI: 10.1017/s0022029905000749
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and partial characterization of a coagulant preparation from Silybum marianum flowers. Its action on bovine caseinate

Abstract: An outstanding parameter in cheese making is the type of coagulant, which greatly influences the characteristics of the final products. Proteolysis is the most important set of biochemical changes during ripening of most cheeses, and is carried out, in different magnitude, by proteolytic agents originated in milk, rennet (or rennet substitute), and starter and non-starter micro-organisms (Silva & Malcata, 2000). The demand for alternative sources of milk coagulants, to replace the expensive and limited natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 8 publications
7
31
0
1
Order By: Relevance
“…Subsequent studies on those species (Esteves, Lucey, Wang, & Pires, 2003;Faro, Veríssimo, Lin, Tang, & Pires, 1995;Llorente et al, 2004) confirmed the presence of aspartic proteases in the extracts and similar results were obtained when other species belonging to the same taxonomic group (tribe Cardueae, family Asteraceae) were analyzed as potential milk coagulants (Tamer, 1993;Vairo Cavalli, Claver, Priolo, and Natalucci (2005)). …”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Subsequent studies on those species (Esteves, Lucey, Wang, & Pires, 2003;Faro, Veríssimo, Lin, Tang, & Pires, 1995;Llorente et al, 2004) confirmed the presence of aspartic proteases in the extracts and similar results were obtained when other species belonging to the same taxonomic group (tribe Cardueae, family Asteraceae) were analyzed as potential milk coagulants (Tamer, 1993;Vairo Cavalli, Claver, Priolo, and Natalucci (2005)). …”
Section: Introductionsupporting
confidence: 64%
“…4), which is the lowest value reported for proteases from species belonging to the tribe Cardueae. Optimum proteolysis was achieved around pH 3.8 for Silybum marianum (Vairo Cavalli et al, 2005), proteinases extracted from Centaurea calcitrapa flowers express maximum activity between pH 4.0 and 5.0 (Domingos et al, 1998), maximum proteolytic activity was recorded at pH 5 for C. scolymus (Llorente et al, 2004), cardosins A and B isolated from flowers of C. cardunculus exhibit maximal activity between pH 5.0 and 5.5 (Faro et al, 1995), while higher peak activity in Australian cardoon (C. Cardunculus) was reached at pH 6.0 (Chen, Zhao, & Agboola, 2003), but in this case casein (not haemoglobin) was used as substrate. Maximum pH value for O. acanthium flowers is even lower than those obtained for calf, pig and lamb chymosins (Foltman & Szecsi, 1998).…”
Section: Enzyme Extract Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is grown also as an ornamental plant (Bhattacharya 2011) and as a tolerant species for soils polluted by heavy metals (Rio-Celestino et al 2006;Perrino et al 2014). In addition, is considered as a new source of plant rennet for aspartic peptidases present in its flowers (Vairo Cavalli et al 2005). Probably due to the plurality of biological activities from its secondary metabolites, milk thistle is also the most studied plant for the treatment of liver disease and this is documented by the huge increase of papers on this topic, over 800 publications, in the last 5 years (Alemardan et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…(Asteraceae), (Vairo Cavalli et al 2005) and the use of its flowers and leaves for the production of small-scale Serpa cheese has been reported (Cabral et al 1984).…”
mentioning
confidence: 99%